DETERMINATIONS OF NATURALIZATION AND ITS IMPACT ON EARNINGS - Kim, Won Joong; Han, Yongseung; Kim, Myeong Hwan (European Scientific Journal, ESJ, 2015)
Many studies about the effects of naturalization on earnings do not account for the endogenous characteristic of naturalization. This study is concerned with the determinants of naturalization, its effect on earnings, and reversal causality between earnings and naturalization. Ordinary least squares (OLS), treatment effect model, and simultaneous equation model are used to estimate the effect of naturalization on earnings for U.S. immigrants. Using a treatment effect model, we find that naturalization has a much higher positive impact than the OLS method on earnings, but by employing a simultaneous equation model, the naturalization premium becomes closer to that of OLS. Also, we find that correcting the simultaneity problem between earnings and naturalization is much more important than orthogonalizing the naturalization variable using instruments.